Autonomic small fiber involvement in painful long COVID: a histological and clinical study - Falco, Pietro; Galosi, Eleonora; Litewczuk, Daniel; Evangelisti, Enrico; Di Stefano, Giulia; Arendt-Nielsen, Lars; Truini, Andrea; Leone, Caterina Maria (Frontiers in Human Neuroscience, 2026)
BackgroundDespite growing recognition of painful long COVID syndrome as a chronic neurological condition marked by pain and autonomic symptoms, the precise contribution of autonomic small fiber involvement is still not well characterized and understood. In this retrospective study, we aimed to identify autonomic small fiber involvement in patients with painful long COVID syndrome by analyzing skin biopsy data. We used nerve fiber density in the piloerector muscles (PMNFD) and sweat glands (SGNFD) as the primary histological outcomes of autonomic innervation.MethodsWe reviewed skin biopsy samples from 50 patients with painful long COVID syndrome and included 31 patients with available PMNFD and SGNFD data for analysis. PMNFD and SGNFD were compared with an age- and sex-matched healthy control group (n = 42). To evaluate whether autonomic involvement was independent of somatic nerve fiber reduction, a subgroup analysis was performed in patients with normal intraepidermal nerve fiber density (IENFD) (n = 23). Correlations between histological findings and autonomic symptoms, assessed with the COMPASS-31 questionnaire, were also analyzed.ResultsPiloerector muscle nerve fiber density and SGNFD were significantly reduced in patients with long COVID compared with controls, both in the full sample (p = 0.0135; p < 0.0001) and in the subgroup with normal IENFD (p = 0.0003; p = 0.0005). Neither PMNFD nor SGNFD correlated with COMPASS-31 scores (p = 0.27; p = 0.46) and no association with disease onset, duration and COVID-19 severity was found.ConclusionThese findings provide histological evidence that autonomic small fiber damage is a prominent and measurable feature of painful long COVID syndrome. Importantly, this pathology was also observed in patients with preserved IENFD, indicating that autonomic involvement may occur independently of somatic small fiber loss.